Assessing supply, demand, and professional development needs of employees in water-related careers - Pieschl, Jordan Marie (Kansas State University, 2017)
STEM fields represent between 5% and 20% of all employed in the United States (United States Department of Labor – Bureau of Labor Statistics, 2015). Many employers of job positions in the STEM field have indicated an ongoing challenge of demand for such employees exceeding supply (Hira, 2010). Literature suggests a skills gap exists in some career fields and labor markets (Sentz, 2013). A topic that falls in many STEM fields in water resources. In Kansas, both supply and demand of water resources vary greatly across the state. A growing trend statewide, however, is a need to focus efforts on preserving the quality and quantity of Kansas’ water supply. Anecdotal evidence suggests the focus on water resources increases the demand for employees prepared for careers in related STEM fields (S. Metzger, personal communication, May 3, 2016). Drawing on both the Human Capital Theory and the Theory of Work Adjustment, descriptive survey research and qualitative interviews based in symbolic interactionism were used to gather data from employers of water-related job positions. The data indicated that a variety of employability and technical skills describe both employers’ ability requirements and employees’ ability sets. The results of the study suggest that, while employers have not recently experienced much challenge filling job vacancies, demand for employees could increase in the near future. Additionally, employers utilize a variety of professional development resources, and would utilize others if available. While levels of correspondence range among ability requirements and ability sets depending on the job position, efforts in education and recruitment could help address the supply of candidates for these positions.
Keywords: Human Capital Theory; Theory of Work Adjustment; STEM professional development needs; skills gap; natural resources education; water